2021
DOI: 10.1523/jneurosci.0027-21.2021
|View full text |Cite
|
Sign up to set email alerts
|

A Signaled Locomotor Avoidance Action Is Fully Represented in the Neural Activity of the Midbrain Tegmentum

Abstract: Animals, including humans, readily learn to avoid harmful and threatening situations by moving in response to cues that predict the threat (e.g., fire alarm, traffic light). During a negatively reinforced sensory-guided locomotor action, known as signaled active avoidance, animals learn to avoid a harmful unconditioned stimulus (US) by moving away when signaled by a harmless conditioned stimulus (CS) that predicts the threat. CaMKII-expressing neurons in the pedunculopontine tegmentum area (PPT) of the midbrai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 47 publications
2
21
2
Order By: Relevance
“…The results of the present study regarding convergence of motor and auditory processing in PPTg strongly support a role in sensorimotor integration. Our findings show that this sensorimotor integration, previously seen in the summed calcium signal from populations of PPTg neurons within (Hormigo et al , 2021), can occur at the single cell level. We found a very high level of convergence of auditory and motor responsiveness, with 81% of reach-related neurons showing tone responses.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The results of the present study regarding convergence of motor and auditory processing in PPTg strongly support a role in sensorimotor integration. Our findings show that this sensorimotor integration, previously seen in the summed calcium signal from populations of PPTg neurons within (Hormigo et al , 2021), can occur at the single cell level. We found a very high level of convergence of auditory and motor responsiveness, with 81% of reach-related neurons showing tone responses.…”
Section: Discussionsupporting
confidence: 65%
“…In addition to motor control functions, many PPTg neurons respond strongly at short latency to auditory, visual, vestibular and somatosensory signals (Grunwerg et al , 1992;Reese et al , 1995;Dormont et al , 1998;Ivlieva & Timofeeva, 2003;Carlson et al , 2004;Pan & Hyland, 2005;Aravamuthan & Angelaki, 2012), consistent with a role in sensory processing. Recently, a fiber photometry study has confirmed that the PPTg region generates calcium signal responses to both auditory warning signal, and during the active avoidance locomotion triggered by the cue (Hormigo et al , 2021). While these responses could reflect activity in separate neural channels within PPTg (Pahapill & Lozano, 2000;Tubert et al , 2019), another possibility is that sensory and motor information may converge at the neuronal level allowing for sensorimotor integration in PPTg.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent paper, we used fiber photometry to compare calcium signals of CaMKII-expressing neurons in the pedunculopontine tegmentum region (PPT) of mice trained in AA1 followed by AA2 (Hormigo et al, 2021a). These neurons show robust activation during performance of signaled active avoidance and are critically required for signaled active avoidance because avoidance is abolished when they are inhibited (Hormigo et al, 2019).…”
Section: Action Caution Occurs Without Frontal Cortex or During Basal...mentioning
confidence: 99%
“…In addition to motor control functions, many PPTg neurons respond strongly at short latency to auditory, visual, vestibular and somatosensory signals (Grunwerg et al , 1992;Reese et al , 1995;Dormont et al , 1998;Ivlieva & Timofeeva, 2003;Carlson et al , 2004;Pan & Hyland, 2005;Aravamuthan & Angelaki, 2012), consistent with a role in sensory processing. Recently, a fiber photometry study has confirmed that the PPTg region generates calcium signal responses to both auditory warning signal, and during the active avoidance locomotion triggered by the cue (Hormigo et al , 2021). While these responses could reflect activity in separate neural channels within PPTg (Pahapill & Lozano, 2000;Tubert et al , 2019), another possibility is that sensory and motor information may converge at the neuronal level allowing for sensorimotor integration in PPTg.…”
Section: Introductionmentioning
confidence: 99%